Motivational Strategy of English Teachers in Promoting the Secondary School Students’ Learning Achievement in English Subject - Khadijah Maming; Sudarmanto Sudarmanto (Musamus Journal of Language and Literature, 2022)
The students’ learning achievement as one of quality indicators from the knowledge acquired and mastered by students. In another side, the students’ learning achievement is the results of educational system, so that the success level determined by its elements, such as students’ motivation as raw input and teachers’ competences as instrument of input. This research aims to find out and analyze the factors involved in teachers’ motivation to support the improvement of students’ learning achievement as well as the development of model of teachers’ motivational strategy in developing the students’ achievement in Junior High Schools. This research was conducted at Junior High School 2 and 12 of Parepare. The research respondents are English teachers nd students. The reserach design used qualitative method. The instruments used were observation, interview and documentation. The findings of this reseracher revealed that factors affect the teachers’ motivation in supporting the students’ achievement covering internal factors and external factors. Internal factors contain the health of physics, psychology, spirit and stable psychoemtional condition. The external factors include physic environment, social of class and social of family. The research data related to development of motivational strategy model of teachers in improving the students’ learning achievement including intelligence, interest, aptitude and creativity. The components related to the teachers’ efforts in instructional process including engaging and activating the students, giving praise, assisting the students’ difficulties, supporting the students to practical activities and avoiding discouraging expressions.